1995
DOI: 10.1108/eb047318
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress, Type‐a Behavior and Employees' Well‐being Among Muslim Immigrants in North America: A Study in Workforce Diversity

Abstract: The present study examined the relationship of job stress and Type‐A behavior pattern with employees' job satisfaction, turnover intention, absence behavior, organizational commitment, psychosomatic health problems, and happiness in life. Data were collected by means of a structured questionnaire from full‐time employed Muslims (N = 325) living in Canada and United States of America. Pearson correlation and moderated multiple regression were the statistical techniques employed to analyze data. Results generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
1
18
1
1
Order By: Relevance
“…The researchers observation based on literature available that role conflict associated with the various variables such as organizational commitment, job involvement, job satisfaction, absenteeism, and turnover intention (Morris & Sherman, 1981;Zahra, 1984;Ismail, 1990;Jamal & Badawi, 1995;Reichers, 1983;Ashforth & Saks, 1996;King et al, 2005;Bettencourt & Brown 2003;Harris et al). Researchers felt that adequate manpower, explicit rules and regulations, instructions, group cohesiveness, adequate resources are required to accomplish the assigned task without any resistance to minimize the role conflict.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers observation based on literature available that role conflict associated with the various variables such as organizational commitment, job involvement, job satisfaction, absenteeism, and turnover intention (Morris & Sherman, 1981;Zahra, 1984;Ismail, 1990;Jamal & Badawi, 1995;Reichers, 1983;Ashforth & Saks, 1996;King et al, 2005;Bettencourt & Brown 2003;Harris et al). Researchers felt that adequate manpower, explicit rules and regulations, instructions, group cohesiveness, adequate resources are required to accomplish the assigned task without any resistance to minimize the role conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that these types of feelings result in increased problems for one's physical well-being (Buttner 1992;Ufuk and Ozgen 2001), psychological well-being (Jamal and Badawi 1995;Naughton 1987;Eden 1975), and satisfaction at work (Buttner 1992;c.f. Naughton 1987).…”
Section: The Identity Distinctiveness Of Entrepreneurial Individualsmentioning
confidence: 99%
“…A stressz következtében fellép a munkahelyi elégedetlenség, az alacsony szervezeti elkötelezettség, a kiégés, a gyakori hiányzás, és a romló munkahelyi teljesítmény (Jamal, 1985;Jamal és Baba, 1997;Jamal és Badawi, 1995;Westman és Eden, 1996).…”
Section: A Munkahelyi Stressz Fogalmaunclassified